Research Progress of Astragalus in the Treatment of Membranous Nephropathy - Men, Niuniu; Tian, Yun (Journal of Contemporary Medical Practice, 2024)
The basic pathogenesis of membranous nephropathy (MN) is the primary deficiency accompanied by solid deficiency. The deficiency of spleen and kidney is the primary and the symptom of rheumatism and stasis. Astragalus is the essential medicine for tonifying spleen and kidney. In the treatment of membranous nephropathy, Astragalus can play the role of tonifying spleen and kidney, detumifying water, dispelling pathogenic wind and promoting blood flow. Its classic formula has also been widely used in the treatment of membranous nephropathy. This article reviews the research status of astragalus in MN treatment.